Hokey Religions: Star Wars and Star Trek in the Age of Reboots. Issue 2 (July 2017) - Canavan, Gerry
Abstract : Disney's recent "decanonization" of the decades-old Star Wars "Expanded Universe" in preparation for the release of The Force Awakens once again raises the question of the triangular relationship between the corporate ownership of intellectual property, the mainstream audience to whom the blockbuster films are addressed, and the much smaller hardcore fanbase whose loyalty sustains a franchise during its lean years. Considering fandom investment in the processes of world-building and continuity construction across the landscape of SF media forms, this article will focus specifically on two key franchises in mainstream SF, each in its own way paradigmatic of the "merely" science fictional, and each of which has recently undertaken a radical revision of its "expanded universe":Star Wars andStar Trek . A concluding discussion extends these observations to other two franchises: Superman comics and the long-running British television series Doctor Who .